CO-REGULATION IN MEXICAN ENVIRONMENTAL LAW (Utah Environmental Law Review; Vol 32 No 2 (2012), 2012)
In the early 1990s, the Mexican federal government began seriously enforcing the country’s environmental laws. Environmental protection had become an issue of political salience with the negotiation of the North American Free Trade Agreement and the occurrence of deadly pollution incidents that made national headlines. Interestingly, at the same time that the government stepped up traditional environmental law enforcement with more frequent inspections and penalties, it also established an alternative co-regulatory approach to enforcement: the National Environmental Audit Program ( Programa Nacional de Auditoria Ambiental , “Audit Program”). Under the Audit Program, participating companies would contract a private auditor to identify instances of non-compliance and then negotiate an agreement with the government for attaining compliance. Upon successful completion of the agreement, the company would receive an eco-label from the government. The Audit Program was maintained and expanded in the 1990s and 2000s. By 2010, about 9,000 facilities throughout the country had participated. The Audit Program is a significant example of the use of environmental co-regulation in an industrializing country. Co-regulation, a regulatory approach that combines elements of state-centered regulation and self-regulation, has been used more commonly in industrialized countries, particularly those in Europe. This Article builds upon past studies of co-regulation to identify the reasons it emerged in Mexico and analyzes how these reasons differ from other countries.